Gender Analysis on CSR Program of Local Economic Empowerment by PT Holcim Indonesia Tbk - Luciani Prastiwi, Debbie; Sumarti, Titik (Sodality: Jurnal Sosiologi Pedesaan, 2012)
Baitul Maal wa Tamwil (BMT) Swadaya Pribumi is Corporate Social Responsibility (CSR) of local economic empowerment by PT Holcim Indonesia Tbk. Gender analysis is used as an analysis tools to see the success rate of BMT Swadaya Pribumi from a gender perspective by understanding the roles (division of labour) in the household, access, control to get resources (credit, training, and mentoring efforts), and the benefits for participants. Quantitatively, BMT is successful and it has considerd gender practical and strategic gender needs are different between the participants of women and men